LINGUACULTURAL CODES - Usmonova Durdona Fazliddin qizi,, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This thesis conceptualizes linguacultural codes as semiotic systems integrating linguistic forms with cultural schemas to construct and negotiate meaning in intercultural communication. Drawing on Lotman’s semiosphere, Wierzbicka’s metalanguage, Lakoff and Johnson’s conceptual metaphor theory, and Brown and Levinson’s politeness framework, it examines indexicality, metaphorical mapping, and pragmatic implicature across English, Russian, and Uzbek. Corpus-based contrastive analysis (Uzbek National Corpus, parallel EN-RU-UZ corpora, Telegram multimodal data) reveals statistically significant divergences in mortality metaphors, temporal spatialization, and emoji interpretation. Neurocognitive evidenceand experimental priming confirm the embodied and adaptive nature of code-switching. Pedagogical interventions in Uzbekistan’s trilingual education yield 34% gains in pragmatic appropriateness. The study advocates code-awareness curricula, positioning linguacultural codes as dynamic bridges between linguistic structure and sociocultural worldview.